Analysis of structural responses of bridges based on long-term structural health monitoring. Issue 1 (2nd January 2018) - Zeng, Lei; Liu, Yiping; Zhang, Ge; Tang, Liqun; Jiang, Zhenyu; Liu, Zejia
ABSTRACT: Structural health monitoring system (SHMS) has been increasingly used for the maintenance of vehicle bridges nowadays. In this paper, a centralized SHMS is developed to monitor multiple bridges. The structural responses of two vehicle bridges in China, including the deformation of main components, creep and shrinkage of concrete, and strain caused by the temperature are estimated and analyzed based on the long-term monitored data. A numerical simulation has been carried out to investigate the deformation of the bridges, as well as the strain and stress on the specific sections. The results show a good agreement with the measured data. Wavelet analysis method has been introduced to investigate the characteristics in time and frequency domain, where the strain components caused by the season temperature variation, daily thermal effects, and random traffic loads can be clearly distinguished as the signals at four levels.